Analysis of the Settlement of Money Political Criminal Actions in the Election of Regional Head in Majene District - Desi Amalia Anwar; Syamsuddin Muchtar; Amir Ilyas (LEGAL BRIEF, 2022)
This study aims to determine and analyze the settlement of Money Politics Crimes in the Regional Head Election in Majene Regency. In this study, the author uses a juridical empirical research method, The legal materials are analyzed using a statutory approach and a conceptual approach. The results of the study indicate that: (1) The process of resolving criminal acts of money politics in the Regional Head Election of Majene Regency is considered not optimal, due to frequent conflicts of opinion related to regulations between the Sentragakkumdu parties, namely Bawaslu, the Prosecutor's Office, and the Police, which is an obstacle for the Agency. General Election Oversight (BAWASLU) in handling cases of money politics. This difference of opinion should not have occurred because the regulations governing the Violation of Money Politics Crimes have been specifically regulated in Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors, which in these rules are very clear on which ones can be categorized as Violations. Money Politics Crime. (2) A person can be held criminally responsible if he has fulfilled the elements or formulation of the offense that has been determined in the laws and regulations. Besides that, the most important thing from criminal responsibility is the existence of errors inherent in the perpetrators.